Parametric Analysis and Optimization of Wire EDM for Improved Surface Roughness of D2 Tool Steel Using Response Surface Methodology - Kharat, Dipak Parasram; Nawathe, Mahendra P. (Zielona Góra: Uniwersytet Zielonogórski)
This study presents a systematic investigation into the optimization of Wire Electrical Discharge Machining (WEDM) parameters for improving the surface finish of D2 tool steel. Utilizing Response Surface Methodology (RSM) integrated with Central Composite Design (CCD), the research aims to minimize surface roughness (Ra) through the controlled variation of critical process parameters: wire feed rate, pulse-on time, pulse-off time, peak current, and sensitivity.
Keywords: WEDM; D2 steel; surface roughness; response surface methodology; central composite design (CCD); optimization